2019
DOI: 10.1039/c9ra06639j
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Cd(ii) coordination polymer encapsulated by Tb3+ as a reversible luminescent probe for Fe3+

Abstract: A new and convenient method for individual identification of Fe3+ ions by the combination of Cd-P and Tb3+@Cd-P was successfully established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The reason for luminescence quenching is that a non-luminescent ground state complex is formed between the nitrogen atoms of Fe 3+ and MOF. [83][84][85][86][87] The IISERP-MOF25 could successfully analyse Fe 2+ and Fe 3+ to achieve the purpose of separation in aqueous solutions, and the LOD towards Fe 3+ was 3.6 ppm. These results indicated that Ln-MOF could act as environmentally benign, cost-effective, scalable, and recyclable sensors.…”
Section: Luminescence Sensing Towards Fe 3+mentioning
confidence: 99%
“…The reason for luminescence quenching is that a non-luminescent ground state complex is formed between the nitrogen atoms of Fe 3+ and MOF. [83][84][85][86][87] The IISERP-MOF25 could successfully analyse Fe 2+ and Fe 3+ to achieve the purpose of separation in aqueous solutions, and the LOD towards Fe 3+ was 3.6 ppm. These results indicated that Ln-MOF could act as environmentally benign, cost-effective, scalable, and recyclable sensors.…”
Section: Luminescence Sensing Towards Fe 3+mentioning
confidence: 99%